High‐Efficiency CO2/N2 Separation Enabled by Rotation of Electrostatically Anchored Flexible Ligands in Metal–Organic Framework. (9th November 2022) - Qu, Kai; Huang, Kang; Xu, Jipeng; Dai, Liheng; Wang, Yixing; Cao, Hongyan; Xia, Yongsheng; Wu, Yulin; Xu, Weiyi; Yao, Zhizhen; Guo, Xuhong; Lian, Cheng; et al.
Abstract: Metal organic frameworks (MOF) are of great potential for molecular separation, but the ligand rotation flexibility makes them remain challenging in the construction of fixed nanochannels for precise sieving. Here we report an electrostatic‐anchoring strategy to fix the rotation of 2‐methylimidazole (2‐MIM) ligand in ZIF‐8. Electrostatic inducer trifluoroacetate anchored at and blocked the six‐membered windows of ZIF‐8, and meanwhile induced the positive 2‐MIM rotated from initial 49° to 68°, thus opening neighbored four‐membered windows with a constant size of 3.4 Å. The obtained ZIF‐8 significantly enhanced the CO2 /N2 adsorption selectivity from 14.02 to 332.86. Further membrane‐based separation exhibited an outstanding CO2 /N2 selectivity of up to 137 with a desired permeability of 286 Barrer, which exceeded the 2019 upper bound. This strategy provides a new inspiration for fixing the ligand rotation in soft MOF for desired precise molecular sieving. Abstract : Flexible rotating ligands in a metal–organic framework (ZIF‐8) can be anchored by electrostatic negative molecules (e.g., CF3 COO − ). Rotation of electrostatically anchored flexible ligands opens four‐membered (4‐M) windows that enable precise CO2 /N2 separation.